Pacemaker-associated infection caused by ST81/SCCmec IV methicillin-resistant, vancomycin-intermediate Staphylococcus aureus in Japan - M. Sakurada; H. Sumi; K. Kaji; N. Kobayashi; Y. Sakai; M.S. Aung; N. Urushibara; N. Kobayashi (New Microbes and New Infections, 2020)
A 76-year-old Japanese man was admitted to hospital for treatment of fever and skin lesion at the implantation site of his pacemaker. During his hospitalization, vancomycin-intermediate Staphylococcus aureus (MIC 4 μg/mL) with reduced susceptibility to daptomycin was isolated from venous blood. This isolate was identified as methicillin-resistant S. aureus with SCCmec IV and was genotyped as sequence type 81, coa VIIa and spa type t7044, harbouring blaZ, aac(6′)-aph(2″) and enterotoxin(-like) genes sea, seb, sek, sel, selx and selw. The patient was successfully treated with daptomycin, minocycline and sulfamethoxazole/trimethoprim. We describe the identification of sequence type 81/SCCmec IV vancomycin-intermediate S. aureus from pacemaker-associated septicaemia.